Developing Kenya’s Educational Capacity in Nuclear Security Through Nuclear Forensics Research - Hudson Kalambuka Angeyo (International Journal of Nuclear Security, 2018)
Nuclear energy’s distinctive characteristics give rise to special educational requirements. These requirements are necessary to not only address the danger of nuclear proliferation, but also to build capacity for a secure nuclear fuel circle. In this paper, I assess the status of educational capacity in nuclear security both in response to, and in support of, Kenya’s nuclear power program. I highlight the nuclear security educational infrastructure’s key features in the context of nuclear power, noting the low capacity at Kenyan universities. I identify the steps required to ensure that the country’s dynamic nuclear regulatory infrastructural framework is used effectively to build capacity in nuclear security. I then examine the link between nuclear security and nuclear forensics and discuss efforts toward developing educational capacity in nuclear security through forensics research at the University of Nairobi, emphasizing in-field nuclear forensics and management of nuclear and radioactive materials out of statutory control. Finally, I consider the research challenges and solutions, which include developing a National Nuclear Forensic Library as a database for illicit trafficking or incidents that involve nuclear and radioactive material. I conclude that, despite the challenges, progress is underway but can be accelerated by promoting broader stakeholder involvement and government buy-in for more comprehensive educational capacity building in nuclear security.
Keywords: Education Capacity; Nuclear Security; Nuclear Forensics